Growing enough food in a changing climate - Beddington, J.R. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
Sir John Beddington, Chief Scientific Adviser to the UK Government, outlines what will be needed to meet global food supply needs despite the impacts of climate change.